Implementation Intentions Related to Self-Regulatory Processes Do Not Enhance Learning in a Multimedia Environment - Hoch, Emely; Scheiter, Katharina; Schüler, Anne (Frontiers in Psychology, 2020)
Learners face various obstacles during learning from illustrated texts that can be conceptualized against the backdrop of frameworks of self-regulated learning. According to these frameworks, for learning to be successful, students must use appropriate cognitive strategies, hold adequate self-efficacy beliefs, and invest sufficient effort in learning. We investigated whether implementation intentions (if-then-plans) relating to these self-regulatory processes improve learning in a multimedia environment, and whether they differ in their effectiveness depending on the self-regulatory process that they address. Learners were either asked to internalize an implementation intention relating to cognitive strategies, self-efficacy beliefs, or effort, or they did not receive any instructional support (control condition). Then, they learned about a mechanical system from a multimedia message, and finally were tested on the learned contents. Contrary to expectations, none of the implementation intentions increased learning outcome, compared with the control condition, nor did the conditions differ from each other. However, implementation intentions interacted with the self-efficacy beliefs that learners already held. Higher self-efficacy beliefs were associated with better learning outcome, unless learners received an implementation intention telling them to use a multimedia-specific cognitive strategy. Interfering cognitive processes are discussed as a possible explanation for this interaction. In sum, implementation intentions should be further investigated and optimized before they can be implemented in real-life learning contexts.